Beneficiation of phosphates : new thought, new technology, new development - Zhang, Patrick; Miller, J. D.; El-Shall, Hassan E. (Society for Mining, Metallurgy, and Exploration, 2012)
Fueled by climbing food prices, the demand for fertilizers is on the rise. The phosphate industry is responding aggressively by bringing signifi cant projects on line across the globe. But meeting this unprecedented demand comes with a host of challenges: Environmental lawsuits have put a stop to one of the largest phosphate mines in the world. Other operations are closing because of the depletion of phosphate reserve. The increasing proportion of high organic and high dolomite ores has caused benefi ciation costs to skyrocket. There is a growing urgency for the sustainable development and recycling of phosphate resources. Beneficiation of Phosphates: New Thought, New Technology, New Development provides a comprehensive look into how industry leaders and the R & D community are responding to these and many other critical issues.